Violence, Discrimination, Psychological Distress, and HIV Vulnerability Among Men Who Have Sex With Men in Memphis, Tennessee. Issue 2 (March 2023) - Denney, Meredith R.; Pichon, Latrice C.; Brantley, Meredith L.
Gay, bisexual, and other men who have sex with men (MSM) are disproportionally impacted by HIV. Discrimination, violence, and psychological distress (PD) may influence engagement with HIV prevention services and amplify HIV vulnerability among this priority population. These dynamics are understudied in the Southern United States. Understanding how these relationships interact is critical to designing effective HIV programs. We examined associations between MSM-related discrimination, MSM-related violence, and severe PD with HIV status among 2017 National HIV Behavioral Surveillance study participants in Memphis, Tennessee. Eligible participants were aged ≥18 years, born and identified as male, and reported having sex with another man in their lifetime. Participants completed a Centers for Disease Control and Prevention–designed anonymous survey and self-reported discrimination and violence across their lifetime, and PD symptoms within the past month, scored on the Kessler-6 Scale. Optional HIV rapid tests were performed on-site. Logistic regressions examined the associations between the exposure variables and HIV antibody-positive results. Among 356 respondents, 66.9% were aged <35 years and 79.5% identified as non-Hispanic Black; 13.2% reported experiencing violence, 47.8% reported discrimination, and 10.7% experienced PD. Of the 297 participants who tested, 33.33% were living with HIV. Discrimination, violence, and PD were significantly associated with each other ( p < .0001). HIV antibody-positive test results were associated with violence ( p < .01). Memphis-based MSM face a complex array of social experiences, which may increase vulnerability to HIV. On-site testing at community-based organizations and clinical settings among MSM may be an opportunity to screen for violence and incorporate strategies when designing HIV programs.